PEMBUATAN POJOK BACA SEBAGAI UPAYA MENINGKATKAN MINAT BACA DAN PEMBELAJARAN DI TK NEGERI 2 BUTON - La Jetia; Manan Manan (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Reading interest is an important foundation in the learning process, especially in early childhood education. However, the lack of supporting facilities such as reading corners is one of the obstacles in fostering reading habits among kindergarten children. This community service program (PKM) aims to increase reading interest and the quality of early childhood learning through the creation of a reading corner at Buton 2 Public Kindergarten. The implementation method includes an initial survey, planning the design of the reading corner, procuring age-appropriate reading materials, and implementing and evaluating joint reading activities. The results of this program show an increase in children's enthusiasm for reading activities and increased teacher involvement in utilizing the reading corner as a learning medium. The reading corner not only serves as a literacy tool, but also creates a fun and interactive learning environment to prevent excessive use of technology that impacts children's literacy skills. This program is expected to become a model for literacy empowerment in early childhood education in other regions.